2023
DOI: 10.1021/acs.inorgchem.3c01579
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis-Controlled Polymorphism and Anion Solubility in the Sodium-Ion Conductor Na3InCl6–xBrx(0 ≤x≤ 2)

Abstract: Motivated by the significant transport property improvement of the anion-substituted lithium metal halides, a series of anion mixed solid solutions of Na 3 InCl 6−x Br x (0 ≤ x ≤ 2) are successfully synthesized by ball milling and subsequent annealing. By milling, the Na 3 InCl 6−x Br x solid solution series crystallizes in a monoclinic P2 1 /n phase, while the subsequently annealed Na 3 InCl 6−x Br x series transforms into a trigonal P3̅ 1c phase. Through annealing and changes of the structure type, greater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The structure and transport properties of ball milled Na 3 InCl 6 have been discussed in-depth in previous reports. 30,32 Meanwhile, ball milled Na 2 ZrCl 6 is a phase mixture of the trigonal and monoclinic polymorphs, 32 which makes it difficult to distinguish the contributions of each phase. Hence in this work, we focus on the cation-mixed Na 3− x In 1− x Zr x Cl 6 solid solutions only, excluding the endmembers from the discussion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure and transport properties of ball milled Na 3 InCl 6 have been discussed in-depth in previous reports. 30,32 Meanwhile, ball milled Na 2 ZrCl 6 is a phase mixture of the trigonal and monoclinic polymorphs, 32 which makes it difficult to distinguish the contributions of each phase. Hence in this work, we focus on the cation-mixed Na 3− x In 1− x Zr x Cl 6 solid solutions only, excluding the endmembers from the discussion.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray diffraction patterns seem analogous with those of annealed compounds in Na 3− x In 1− x Zr x Cl 6 and ball milled Na 3 InCl 6 with a monoclinic phase (space group P 2 1 / n ). 30,31 However, nominal Na 2.05 In 0.05 Zr 0.95 Cl 6 is an exception, where an additional reflection at ∼1.47 Å −1 (Fig. S2†) is observed in its X-ray diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential structural disorders may be one of the factors contributing to the high ionic conductivities of Na M OCl 4 , as previous studies have commonly observed that a less-ordered structure facilitates Na + movement in halide-based sodium ionic conductors. ,, The ionic conductivities of NaNbOCl 4 and NaTaOCl 4 are at least 2 orders of magnitude higher than those of pristine sodium metal chlorides (Figures c), such as Na 2 ZrCl 6 (∼1.8 × 10 –5 S m –1 ) and Na 3 M Cl 6 -type halides (e.g., ∼2.3 × 10 –8 S cm –1 for M = In, ∼1.0 × 10 –9 S cm –1 for M = Er), ,, except the highly amorphous NaTaCl 6 synthesized under extreme ball milling conditions (∼4 mS cm –1 ) . The values are also much higher than those of cation substituted sodium chlorides, for instance, Na 2.25 Zr 0.75 Y 0.25 Cl 6 and Na 2.4 Zr 0.6 Er 0.4 Cl 6 with ionic conductivities of 6.6 × 10 –5 and 3.5 × 10 –5 S cm –1 . , Just mixing halogen in sodium metal halides (e.g., Na 3 InCl 6– x Br x ) also cannot significantly enhance ionic conductivity . However, the O and Cl dual-anion systems beyond the pure halide system show ionic conductivities of over 1 mS cm –1 , not only NaNbOCl 4 and NaTaOCl 4 , but also 0.5Na 2 O 2 –TaCl 5 glass (4.6 mS cm –1 ), indicating the significance of extending composition systems of halide-based sodium ionic conductors.…”
mentioning
confidence: 93%
“…Since Asano et al discovered the chloride solid electrolyte Li 3 YCl 6 with high oxidation stability, various chloride-based solid electrolytes have been reported. Compared to lithium-ion conducting chlorides, fewer sodium-ion conducting chlorides have been developed (e . g., Na 2 ZrCl 6 , 1.8 × 10 –5 S cm –1 at 30 °C; NaAlCl 4 , 3.9 × 10 –6 S cm –1 at 30 °C; Na 3 YCl 6 , 9.5 × 10 –8 S cm –1 at room temperature; Na 3 InCl 6 , 10 –8 S cm –1 at 100 °C). ,, The conductivities of the end-member of the chloride-based solid electrolytes are necessary for practical use to improve. In general, aliovalent substitution is a typical strategy for increasing the conductivity.…”
mentioning
confidence: 99%